Indian-derived sediments deposited in Australia during Gondwana assembly - Yao, Weihua; Li, Zheng-Xiang; Spencer, Christopher; Martin, E. (Elsevier BV, 2018)
© 2018 Sedimentary exchanges across continents during the collisional assembly and lifespan of supercontinents provide a powerful way of testing the assembling process and configuration of supercontinents. The Ord Basin in north-western Australia contains mid-Cambrian shallow marine and deltaic sedimentary successions that post-date the ca. 650–520 Ma Paterson-Petermann Orogeny (PPO) but are synchronous with the ca. 530–470 Ma Kurgiakh Orogeny in north India. We report new U-Pb ages and Hf isotopes of detrital zircons from the mid-Cambrian Ord Basin that suggest Indian-derived sedimentary input to Australian Cambrian basins. Compilations of published Ediacaran-Ordovician samples from the Centralian Superbasin indicate that during the ca. 650–520 Ma PPO, the 1200–1100 Ma Musgrave province in central Australia was exhumed and fed sediments to the syn-PPO Centralian Superbasin. Soon after the PPO termination, the Musgrave province likely remained a topographic high and continued to supply detritus to the Amadeus and Officer basins that were fragmented from the Centralian Superbasin, supplemented by the ~630 Ma granites of the Paterson orogen. Conversely, we conclude that the mid-Cambrian Ord Basin did not record similar sedimentary provenance from the Musgrave province. Rather, Indian-derived detritus travelled along the northeastern Gondwanan continental margin via longshore currents, and in turn incorporated Paterson granitic detritus, during the assembly of Gondwana (including the Kurgiakh Orogeny in north India). A broad provenance comparison between potential eastern Gondwanan source regions and relevant Asian neighbours suggests that South China and South Qiangtang are affiliated with northern India, but Lhasa appears to have had a mixed affiliation between India and Australia.